(3bGYOI aj GdbQBf hcdGe Gddg JYGdis - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fSJYjfg hfSJZaQI bGYOI ai GdbQBf hcdGe Gddg JYGdi aEf GdCeI EVWQHJ ai gPG EVWQGHkG YXjekG deG MOKJ ajge GdLgejI GdeTJbI ef GdUGHFI s
(3BNQgG (B:s
(3bhdg JYGdi (B( (3Bde Pdc GdcJGH dGQjH ajg (B) (3hfMh Pdc gh cdGe Gddg dGcdGe ZjQg hcdGe Gddg gh eG Jcde Hg dG eG Ndbg ai ZjQg hde jJcde Hg gh s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds